Study on Influencing Factors of Asphalt-Aggregate Stripping Mechanism. (8th February 2021) - Wang, Fuyu; Li, Yan; Yu, Liting; Pang, Weichen
Abstract : In order to study the stripping mechanism of asphalt aggregate comprehensively, the conditions of the stripping of asphalt aggregate are divided into two types, which are anhydrous environment and water environment. The stress generation and release of asphalt film under anhydrous environment and the differences in stripping mechanism of asphalt film under tensile and pressure stress were analyzed. The existence of water in the mixture and its harmfulness to stability were also described in this paper. Moreover, the transport behavior of water in asphalt was studied by the principles of electrochemical testing. The test results show that the diffusion rate of water in modified asphalt film is one half of that of base asphalt, so the blocking water ability of modified asphalt is better than that of matrix asphalt. Moreover, the condition of water spalling the asphalt-aggregate interface is characterized by a change in the mass of asphalt film before and after boiling. It can be concluded that the mass loss of asphalt film is minimal with limestone and modified asphalt, which shows that it has the best spalling resistance.